Antecedents and Consequences of Muslim Millennials Attitude Towards Halal Personal Care Products - Mahliza, Febrina; Nugroho, Lucky; Ali, Anees Jane Ali (IKONOMIKA, 2020)
In Indonesia, the millennial generation is the generation that dominates the population. This is a promising target market for companies or producers of personal care products. This research focuses on the attitudes of the millennial generation towards halal personal care products. The method used is quantitative research with primary data taken from 143 millennial generation female consumer respondents in Jakarta and Tangerang with data collection techniques using purposive sampling. The data analysis used is Partial Least Square (PLS) analysis. Based on the results, the attitude of the millennial generation towards halal personal care products is significantly influenced by religiosity and halal knowledge. At the same time, media exposure has no significant influence on the attitude of the millennial generation towards halal personal care products.